Inflammatory and Neuropathic Nociception is Preserved in GPR55 Knockout Mice - Lawrence M. Carey (Nature Portfolio, 2017)
Abstract The G-protein coupled receptor GPR55 has been postulated to serve as a novel cannabinoid receptor. A previous report indicated that GPR55 knockout mice fail to develop mechanical hyperalgesia, suggesting a pro-nociceptive role for GPR55 in the control of nociceptive responding. However, GPR55 knockout mice remain incompletely characterized in models of pathological pain. Here we provide a comprehensive assessment of responses of GPR55 knockout and wild-type mice to mechanical and thermal (heat, cold) stimulation in multiple, mechanistically distinct models of inflammatory and neuropathic pain. Inflammatory sensitization was produced by intraplantar administration of capsaicin, formalin or complete Freund’s adjuvant. No differences in responding were detected between GPR55 knockout and wild-type mice in any model of inflammatory nociception assessed. Neuropathic pain was induced by partial sciatic nerve ligation (which induces hypersensitivity to mechanical, cold and heat stimulation) or by treatment with the chemotherapeutic agent paclitaxel (which induces hypersensitivity to mechanical and cold stimulation only). No differences were observed between GPR55 knockout and wild type mice in either development or maintenance of neuropathic nociception in either neuropathic pain model. In conclusion, genetic deletion of GPR55 did not alter the development of pathological pain in adult mice in any chronic pain model evaluated.